Application of Seasonal Autoregressive Integrated Moving Average (SARIMA) Method in Forecasting Chicken Egg Prices in Indonesia - Wardah Hasna Afifah; Devni Prima Sari (MUST: Journal of Mathematics Education, Science and Technology, 2025)
Chicken eggs are one of the widely known food commodities and are routinely used for daily food menus. Therefore, the price often fluctuates. So that the forecasting of chicken egg prices in Indonesia is very necessary so that the government can monitor price stability and plan future steps. The method that is suitable for this forecast is the Seasonal Autoregressive Integrated Moving Average (SARIMA). The results of data analysis using the SARIMA method show that the best model used for forecasting is SARIMA (2,1,3)(0,1,1)12. This model has a Mean Square Error value of 815267 and a Mean Absolute Percentage Error of 4% so it is good for forecasting. From this model, it is estimated that the price of broiler chicken eggs will tend to fluctuate and increase in the next 24 months, namely from January 2025 to December 2026. Keywords: price, chiken eggs, forcasting, sarima method.